ANALISIS PENGARUH PENGUMUMAN PEMBAGIAN DIVIDEN TERHADAP ABNORMAL RETURN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Sumani Sumani; Dinda Larasati (Jurnal Akuntansi, 2017)
This study aims to determine the effect of the dividend's announcement to abnormal return from companies that registered in the Indonesia Stock Exchange. The study conducted by calculating the abnormal return by testing the hypothesis by using samples of 14 companies that registered IPO (Initial Pubilic Offer) on the Indonesian Stock Exchange in 2013-2015. From the analysis conducted, showed that there is significant effect between the announcement of the dividend’s announcement of the abnormal return. The result came out from the significant abnormal return that happen before, during and after the event's date.